Forge - Anderson, Laurie Halse (Anderson, Laurie Halse. Seeds of America., 2010)
Separated from his friend Isabel after their daring escape from slavery, fifteen-year-old Curzon serves as a free man in the Continental Army at Valley Forge until he and Isabel are thrown together again, as slaves once more.